2014
DOI: 10.1177/1934578x1400900914
|View full text |Cite
|
Sign up to set email alerts
|

An HPLC Evaluation of Cytochalasin D Biosynthesis by Xylaria arbuscula Cultivated in Different Media

Abstract: A quantitative profile of cytochalasin D production by Xylaria arbuscula was followed by growing the fungus in rice, Czapek, Czapek enriched with yeast extract, wheat, and corn. This cytochalasin producer, X. arbuscula, was collected as an endophytic fungus from healthy tissues of Cupressus lusitanica (Cupressaceae). A new HPLC method was developed using a synthetic N-acetyl-L-phenylalanine ethyl ester as internal standard, which showed a good correlation coefficient (r 2 = 0.9995). The results varied from 6.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The product ion of labeled [M + H] + (Fig. E) revealed the intact incorporation of 2‐ 13 C‐phenylalanine, considering that the ions at m / z 121 and 147 retain the labeling, in agreement with Vederas et al Thereby, we are able to assume these fragment ions as diagnostic ions for cytochalasins derived from phenylalanine, which allow a fast and reliable detection of these molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product ion of labeled [M + H] + (Fig. E) revealed the intact incorporation of 2‐ 13 C‐phenylalanine, considering that the ions at m / z 121 and 147 retain the labeling, in agreement with Vederas et al Thereby, we are able to assume these fragment ions as diagnostic ions for cytochalasins derived from phenylalanine, which allow a fast and reliable detection of these molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The fungus Xylaria arbuscula , isolated from healthy leaves of Cupressus lusitanica , has shown a remarkable ability to produce cytochalasins, mainly cytochalasins D, C and Q (Fig. ) which were identified by mass spectrometry and 1D and 2D NMR analyses . We previously studied the production of these compounds in different media containing rice, corn, wheat and Czapek enriched with yeast extract and found that amino acid‐rich medium, not only phenylalanine, contributes for cytochalasin enhancement …”
Section: Introductionmentioning
confidence: 99%
“…The production of cytochalasin D has been reported by fungi in the genus Xylaria , as X. hypoxylon , 15 X. mellisii , 38 Xylaria sp. , 39 X. carpophila , 40 X. cubensis , 41 X. arbuscula 42 and Xylaria sp. NC1214, a fungal endophyte of the moss Hypnum sp.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Members of the genus Xylaria, which accounts for more than 300 species, are ubiquitous as endophytes in vascular plants. 5 Xylaria have received special attention due to their potential as a source of novel secondary metabolites including terpenoids, 6,7 cytochalasins, [8][9][10] polyketides, 11,12 and peptides, 13,14 many of which possess pharmacological activity and potential for medical application. 11 Safe morphological identification of the producing Xylaria at the species level is, however, difficult because of the poor conservation of morphological characteristics and their intimate association with different stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…19,22,23 The chemical profile of X. arbuscula, regarding secondary metabolite production, as well as its potential for biotransformation reaction, has already been explored. 10,25,26 For the first time, the present work aims to trace the X. arbuscula profile of peptides and proteins in attempt to identify the microorganism by linear mode MALDI-TOF MS.…”
Section: Introductionmentioning
confidence: 99%